Analysing Sports Data with the Casio CFX9850G Colour Graphics Calculator - Clarke, S. R.; Clarke, K. B. (1997)
The use of sporting examples to motivate and interest students in mathematics has long been advocated (Clarke 1984, 1986, 1988, 1990a, 1990b, 1993; deMestre, 1987, 1992). Examples of this approach in data analysis are Clarke and Tobin (1993) and Clarke (1994, 1995). At the time it was necessary to perform such analysis on a computer with a dedicated statistical package such as MINITAB or SAS/JMP. However, with their increase in power and funcionality, graphics calculators can now be used to analyse quite large data sets. Modern graphics calculators will perform a range of statistical functions. These include calculating single and two variable statistics, plotting a range of graphs such as normal curves, histograms, box plots and scatter plots, and fitting straight line and other lines of best fit to data. Like all electronic equipment, newer models are both more sophisticated and cheaper than previous ones. The latest edition to the Casio range is the colour model CFX-9850G, which uses a 3 colour display. In addition to many other functions, its data handling abilities include sorting and calculating with lists, graphing histograms, scatter plots, box plots and normal curves, and calculating single and two variable statistics and several types of regression lines. Also released was a lower level entry model, the FX7400, which should alleviate some of the equity concerns of teachers, and see graphics calculators become available to students in the lower secondary levels. While the screen dumps and calculations here are from the 9850, similar output could be obtained from the 7400.